Impact of acute toxicities associated with chimeric antigen receptor (CAR) T-cell therapy on health-related quality of life (HRQOL) in relapsed or refractory (R/R) large B-cell lymphoma (LBCL). Issue 28 (1st October 2022) - Patrick, Donald; McManus, Shauna; Podger, Lauren; Saunders, Ashley; Braverman, Julia; Liu, Fei Fei; Keating, Scott J.
Abstract : 294 Background: TRANSCEND NHL 001 (TRANSCEND; NCT02631044) evaluated efficacy and safety of the CAR T cell therapy lisocabtagene maraleucel (liso-cel) as third-line or later treatment in patients with R/R LBCL. Prior research demonstrated improvements in HRQOL with liso-cel; however, evidence of HRQOL in the context of CAR T cell‒specific adverse events was not evaluated. In TRANSCEND, the incidence of all-grade cytokine release syndrome (CRS) and neurological events (NE) was 42% and 30%, respectively. This analysis examined longitudinal HRQOL in the presence of CRS and NEs among clinical responders. Methods: Patients in TRANSCEND who responded to liso-cel treatment (n = 137) were stratified into 3 groups: no CRS or NEs, either CRS or NEs but not both, and both CRS and NEs. HRQOL was evaluated with the European Organisation for Research and Treatment of Cancer core quality of life questionnaire (QLQ-C30) and EQ-5D-5L. Summary statistics and change from baseline (liso-cel infusion; CFBL) were calculated for each time point. Results: For liso-cel‒treated patients who responded to treatment and developed CRS, NEs, or both, clinically relevant QLQ-C30 functional (physical, role, and cognitive) and fatigue scores indicated a noticeable nadir (low point) around 1 month post-baseline after liso-cel infusion, followed by a trend toward restoration of baseline status, generally achieved by 2 months after baseline. The primary difference between CRS/NE subgroups appeared to be the extent of decline or depth of the nadir. Patients with no CRS or NEs after liso-cel infusion did not experience an initial decrease in HRQOL/increase in symptom severity and instead showed a trend toward improvement over time (Table; QLQ-C30 fatigue as an illustrative example). This was also observed for EQ-5D-5L index scores. Conclusions: These findings support the anecdotal clinical experience that CRS/NEs are not associated with any long-term detriment in overall HRQOL and indicate a need for discussion with patients before treatment and early symptom monitoring and management of CRS or NEs. Clinical trial information: NCT02631044. QLQ-C30 fatigue scores over time. QLQ-C30 fatigue scores (lower scores indicate less fatigue) No CRS or NEs (n = 67) Either CRS or NEs (n = 36) CRS and NEs (n = 34) Baseline, mean (SD) 36.0 (22.1) 31.8 (16.0) 46.7 (24.0) Month 1, mean (SD) 27.4 (20.1) 34.6 (25.8) 49.1 (25.6) Mean CFBL (SD) −6.35 (19.5) 3.27 (28.1) 2.87 (30.2) Month 2, mean (SD) 22.8 (19.2) 25.1 (20.9) 28.8 (21.8) Mean CFBL (SD) −12.87 (19.3) −7.17 (22.7) −16.67 (31.4) Month 6, mean (SD) 31.0 (26.9) 26.1 (12.1) 27.3 (20.2) Mean CFBL (SD) −4.76 (28.2) −7.78 (19.8) −16.16 (33.4) Month 12, mean (SD) 22.2 (25.5) 25.2 (20.8) 21.6 (12.9) Mean CFBL (SD) −13.53 (23.4) −8.15 (23.2) −27.16 (31.7) SD, standard deviation.